CisCross: A gene list enrichment analysis to predict upstream regulators in Arabidopsis thaliana - Lavrekha, Viktoriya V.; Levitsky, Victor G.; Tsukanov, Anton V.; Bogomolov, Anton G.; Grigorovich, Dmitry A.; Omelyanchuk, Nadya; Ubogoeva, Elena V.; Zemlyanskaya, Elena V.; Mironova, Victoria (Frontiers in Plant Science, 2022)
Having DNA-binding profiles for a sufficient number of genome-encoded transcription factors opens up the perspectives for systematic evaluation of the upstream regulators for the gene lists. Plant Cistrome database, a large collection of transcription factor binding profiles detected using the DAP-Seq method, made it possible for Arabidopsis. Here we re-processed raw DAP-Seq data with MACS2, the most popular peak caller that leads among other ones according to quality metrics. In the benchmarking study, we confirmed that the improved collection of transcription factor binding profiles supported a more precise gene list enrichment procedure, and resulted in a more relevant ranking of potential upstream regulators. Moreover, we consistently recovered the transcription factor binding profiles that were missing in the previous collection of DAP-seq peak sets. We developed the CisCross web service (https://plamorph.sysbio.ru/ciscross/) that gives more flexibility in the analysis of potential upstream transcription factor regulators for Arabidopsis thaliana genes.